Pemberian Ganti Rugi Oleh Pemerintah Akibat Pembangunan Jalan Tol Kediri-Tulungagung - Ramadani Dimas Pamungkas; Deandra Myana Rahayu; Syafa Nabila Azzahra; Fadia Amanda Pertiwi; Hany Nurpratiwi (Pusat Riset dan Inovasi Nasional, 2023)
The objectives of the National Agrarian Law are in line with the objectives of the 1945 Constitution of the Republic of Indonesia as the legal foundation for the formation of the UUPA, namely